Введення в культуру in vitro різних сортів сої (Glycine max (L.) Merr.), стерилізація та динаміка калюсоутворення - Забейда, О.Ф.; Жук, В.П.; Науменко, В.Д. (Фактори експериментальної еволюції організмів, 2015)
Aims. The aim of this study was the selection of the optimal culture conditions for introduction in vitro of different ukrainian soybean varieties (“Horol”, “Tanais”, “Terek”, “Kuban”, “Cheremosh granit”) and the investigation of callus formation on different types of explants. Methods. Нypocotyls, internodes and embryos as explants were used. The highest frequency of callus formation was observed for soybean explants such as hypocotyls and embryos (varieties “Horol”, “Tanais”, “Kuban”) on the medium S1, S2, S3. Callus growth did not occur on the medium S4, S5, S6. Results. The highest frequency for induction of callus was observed for soybean varieties «Horol», «Tanais», «Kuban» on the culture medium S1, S2, S3. Conclusions. It was found that the effectiveness of callus formation depended of the mineral and phytohormonal medium composition, type of explants and explants growth place Hypocotyls and embryos as explants were more effective for callus induction than internodes. Medium S1 was the best medium for callus induction. Keywords: Glycine max (L.) Merr., in vitro culture, callus induction.